1988
DOI: 10.1007/bf03010851
|View full text |Cite
|
Sign up to set email alerts
|

The effects of shivering on oxygen consumption and carbon dioxide production in patients rewarming from hypothermic cardiopulmonary bypass

Abstract: Oxygen consumption (r carbon dioxide production ('(/C02). end-t~dat carbon dioxide partial pressure (PETC02), mixed venous oxygen saturation (S;'02) and haemodynamic variables were recorded every 30 rain for four hours in 1_5 patients recovering from hypothermic cardiopulmonary bypass (CPBFollowing hypothermic cardiopulmonary bypass (CPB), patients usually arrive in the Intensive Care Unit (ICU) with a nasopharyngeal temperature (NPT) of 34-36 ' C. t Sladen et al. showed that over the subsequent 8 hr patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(26 citation statements)
references
References 11 publications
0
25
0
1
Order By: Relevance
“…The clinical consequences of shivering can include increased tissue ischemia, which has been associated with increased morbidity in postoperative patients who have undergone cardiac surgery. 25 We have shown that shivering during therapeutic normothermia is associated with lower Glasgow Coma Scale scores in neurocritical care patients, which most likely reflects the sedation required to adequately treat shivering. 15 The ability to titrate antishivering therapy with short-acting opioids or other sedative agents to a BSAS score of 1 might provide allow clinicians to eliminate harmful levels shivering without oversedating.…”
Section: Badjatia Et Al Metabolic Impact Of Shivering 3245mentioning
confidence: 83%
“…The clinical consequences of shivering can include increased tissue ischemia, which has been associated with increased morbidity in postoperative patients who have undergone cardiac surgery. 25 We have shown that shivering during therapeutic normothermia is associated with lower Glasgow Coma Scale scores in neurocritical care patients, which most likely reflects the sedation required to adequately treat shivering. 15 The ability to titrate antishivering therapy with short-acting opioids or other sedative agents to a BSAS score of 1 might provide allow clinicians to eliminate harmful levels shivering without oversedating.…”
Section: Badjatia Et Al Metabolic Impact Of Shivering 3245mentioning
confidence: 83%
“…Consequently, mild perioperative hypothermia lengthens postoperative recovery -even when temperature is not a criterion for transfer [74] . Shivering occurs postoperatively in 40 % of unwarmed patients [56] and is correlated with adrenergic activation [29] and discomfort [69,100] .…”
Section: Effects Of Mild Perioperative Hypothermiamentioning
confidence: 99%
“…The association of fever reduction with reduction of systemic oxygen consumption, however, is challenged by the variability of responses from prior clinical studies [16,21,22]. The work by Manthous et al showed a significant reduction of systemic VO2 with fever reduction in the setting of hypoxemic, hypercapneic, or shock-related respiratory failure [16].…”
mentioning
confidence: 96%